639.HYDRAULIC LOADER CRANE – OPERATOR WORKPLACE RISK ASSESSMENT - Atila, Zelic; Dragan, Zivanic; Nikola, Ilankovic; Mirko, Katona; Kristina, Jakimovska; Anita, Vasileva; Natasa, Antic (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
The aim of this paper is to assess the risk to health and safety at work while working with a hydraulic crane mounted on a truck. After the risk assessment, appropriate preventive measures for healthy and safety of work are prescribed, together with a short manual on health and safety at work. The expert finding of the hydraulic loader crane was processed according to the Ordinance on the Manner and Procedure of Risk Assessment at the Workplace and in the Work Environment (Official Gazette of Republic of Serbia, no. 114/2014 and 102/2015).